(untitled) (ADMPG Journal, 2025)
This study conducts a systematic review of the literature on the adoption of smart home technologies, exploring the benefits, barriers, and factors that influence the acceptance of these technologies by consumers. Smart homes, equipped with connected technologies such as monitors, sensors, and network devices, allow automation and remote management of the home environment, promoting efficiency and quality of life. Large companies lead a timid market, while academia seeks to better understand the impact of these technologies. Despite early adopter-driven early growth, mass adoption still faces challenges, including technological complexity and acceptance barriers. This study aims to provide a comprehensive overview of the barriers and benefits to guide future market research and strategies, highlighting the need for user-centric and sustainable solutions.